Vitamin -D Deficiency: A Clinical Problem Searching For Solution. - Ashique, Ali Arain; Syed, Muhammad Ali; Madiha, Shah (Journal of Advanced Pharmaceutical Science And Technology, 2018)
The role that Vitamin D plays in human health is no more hidden in this modern age where every individual carries the knowledge treasure in the pocket (The internet) but the unjustified deficiency or insufficiency is still a research question waiting for the answer from research community all over the world. Normal levels (30-50 ng/ml) are necessary for the development of teeth and bones in children and bone mineralization in adults. The deficiency or insufficiency causes rickets, arthralgia, arthritis, osteoporosis and Osteomalacia. Study Design: Observational study. Study Setting: Department of Orthopedic LUMHS Jamshoro. Study Duration: from April 2017 to Oct 2017. Sampling: 600 patients were selected through Consecutive sampling. Statistical Analysis: Descriptive statistics like mean, Standard deviation, minimum, and maximum were calculated Using SPSS version 22.Mean of two genders was compared using t-test setting <0.05 as level of significance. Results: Mean serum vitamin –D level was 16.11+10.07ng/ml in men while it was 16.63+11.73 ng/ml in women. 62% of the study population was found deficient (<20ng/ml) while 16.33% were having insufficient levels (<30ng/ml) and only 12% showed normal levels (30-50ng/ml). There was no significant difference between the two genders, p value 0.59 Conclusion: Vitamin –D deficiency is very common in both genders with no significant difference between males and females.
Keywords: Vitamin-D; Osteoporosis; Arthritis; Rickets